Tuning the Selectivity of the Hydrogenation/Hydrogenolysis of 5‐Hydroxymethylfurfural under Batch Multiphase and Continuous‐Flow Conditions. Issue 13 (28th June 2022) - Rodríguez‐Padrón, Daily; Perosa, Alvise; Longo, Lilia; Luque, Rafael; Selva, Maurizio
Abstract: The hydrogenation/hydrogenolysis of 5‐hydroxymethylfurfural (HMF) has been carried out either under single (aqueous) phase or batch multiphase (MP) conditions using mutually immiscible aqueous/hydrocarbon phases, 5 % Ru/C as a catalyst, and both with and without the use of trioctylmethyl phosphonium bis‐(trifluoro methane) sulfonimide ([P8881 ][NTf2 ]) as an ionic liquid (IL). Alternatively, the hydrogenation of HMF was explored in the continuous‐flow (CF) mode with the same catalyst. By changing reaction parameters, experiments were optimized towards the formation of three products: 2, 5‐bis(hydroxy methyl)furan (BHMF), 2, 5‐bis(hydroxymethyl)tetrahydrofuran (BHMTHF), and 1‐hydroxyhexane‐2, 5‐dione (HHD), which were obtained in up to 92, 90, and 99 % selectivity, respectively, at quantitative conversion. In particular, the single (aqueous) phase reaction of HMF (0.2 m ) carried out for 18 h at 60 °C under 30 bar of H2, allowed the exclusive synthesis of BHMF from the partial (carbonyl) hydrogenation of HMF, while the MP reaction run at a higher T and p (100 °C and 50 bar) proved excellent to achieve only HHD derived from a sequence of hydrogenation/hydrogenolysis. It is worth noting that under MP conditions, the catalyst was perfectly segregated in the IL, where it could be recycled without any leaching in the aqueous/hydrocarbon phases. Finally, the hydrogenation of HMF was explored in a H‐Cube® flow reactor in the presence of different solvents, such as ethyl acetate, tetrahydrofuran, and ethanol. At 100 °C, 50 bar H2, and a flow rate of 0.1 mL min −1, the process was optimized towards the formation of the full hydrogenation product BHMTHF. Ethyl acetate proved the best solvent. Abstract : Choose your path : Two strategies are explored for the upgrading of 5‐hydroxymethylfurfural (HMF) by hydrogenation/hydrogenolysis in batch multiphase and continuous‐flow systems. To the best of our knowledge, the present work constitutes the first example on the synthesis of 1‐hydroxyhexane‐2, 5‐dione employing an ionic liquid‐assisted multiphase system, not only reaching high conversion and selectivity but also allowing catalyst/product separation.